Teenage predictors of participation of adults with cerebral palsy in domestic life and interpersonal relationships: A 13-year follow-up study. (January 2020) - van Wely, Leontien; van Gorp, Marloes; Tan, Siok Swan; van Meeteren, Jetty; Roebroeck, Marij E.; Dallmeijer, Annet J.
Highlights: In individuals with cerebral palsy: Parenting style and personality predict adult participation. Teenage gross motor capacity predicts adult participation in domestic life. Teenage coping predicts adult participation in interpersonal relationships. Abstract: Background: Adults with cerebral palsy (CP) may experience problems with participation in domestic life and interpersonal relationships. Aims: To identify teenage predictors of adult participation in domestic life and interpersonal relationships. Methods and procedures: This 13-year follow-up of the PERRIN 16-24 cohort included 53 adults with CP without intellectual disability [current age 31.7 (SD = 1.4) years]. Participation performance was assessed as attendance (Vineland Adaptive Behavior Scales), and difficulty/assistance with participation (Life Habits questionnaire). 56 teenage factors were categorized in ICF components. Stepwise multiple linear regression analyses explored predictors of participation. Outcomes and results: Lower gross motor capacity, following special education, having protective parents and a rigid personality predicted less participation in domestic life. Having rejective parents, receiving little daily support, having a socially avoidant personality or coping style and the male gender predicted less participation in interpersonal relationships. Lower activity and participation levels as a teenager predicted less participation in both domestic life and interpersonal relationships of adults with CP. Conclusions and implications: Environmental and personal factors, gross motor capacity and teenage participation were predictors of participation of adults with CP. These factors help identify subgroups at risk for suboptimal adult participation and provide targets for rehabilitation.